2021
DOI: 10.1097/brs.0000000000003990
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Bone Scalpel (USBS) Does Not Reduce Blood Loss During Posterior Spinal Fusion (PSF) in Patients with Adolescent Idiopathic Scoliosis (AIS)

Abstract: Study Design. Randomized Clinical Trial.Objective. The aim of this study was to compare the efficacy of USBS with standard-of-care surgical instruments during posterior spinal fusion (PSF) in patients with adolescent idiopathic scoliosis (AIS) by evaluating the difference in estimated blood loss per level fused (EBL/level). Summary of Background Data. PSF surgery for AIS is often associated with high blood loss. Use of an ultrasonic bone scalpel (USBS) has been proposed to reduce blood loss during scoliosis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…They concluded that UBS is effective in reducing blood loss in AIS and NMS deformity correction surgery. However, Garg et al [37] in their singleblinded randomized control trial had concluded that there was no clinically significant difference in total blood loss, EBL/level, or complications between the AIS undergoing posterior spinal fusion (PSF) and control group. In contrast to reports from other centers, UBS did not lead to reduced blood loss during PSF for AIS.…”
Section: Deformity Correctionmentioning
confidence: 99%
“…They concluded that UBS is effective in reducing blood loss in AIS and NMS deformity correction surgery. However, Garg et al [37] in their singleblinded randomized control trial had concluded that there was no clinically significant difference in total blood loss, EBL/level, or complications between the AIS undergoing posterior spinal fusion (PSF) and control group. In contrast to reports from other centers, UBS did not lead to reduced blood loss during PSF for AIS.…”
Section: Deformity Correctionmentioning
confidence: 99%
“…yakın zamanda yayınladığı çalışmaları ile benzer sonuçlar elde etmiştir. 11 Bartley ve ark çalışmalarında ultrasonik kesicilerin cerrahi süreyi kısalttığını bildirmişlerdir. 12 Wahlquist ve ark.…”
Section: çAlışmaunclassified
“…9,10 Literatürde ultrasonik kemik kesicilerin kanama miktarını azalttığını bildiren çalışmalar olduğu gibi; kan kaybı bakımından etkisiz olduğunu bildiren çalışmalar da mevcuttur. 8,11 Ultrasonik kemik kesicilerin cerrahi süreye etkisi olmadığını bildiren çalışmalar da vardır. 11 Çalışmamızın amacı ultrasonik kemik kesici kullanılarak cerrahi tedavi uygulanan hastalar ile klasik el osteotomlarıyla osteotomi uygulanan hastaları, cerrahi süre ve kan kaybı miktarı bakımından karşılaştırarak literatüre katkı sağlamaktır.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Posterior pedicle screw internal fixation is the main surgical technique for adolescent idiopathic scoliosis (AIS). This surgical technique can greatly improve spine curvature and clinical outcomes, but it usually requires a long surgical incision and multilevel fixation and thus may result in a large amount of blood loss [ 1 , 2 ]. Massive blood loss may prolong the period of incision healing and recovery, increase the risk of infection, and even cause organ failure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%